2000
DOI: 10.1007/s005860000142
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology of idiopathic scoliosis: biomechanical and neuromuscular factors

Abstract: The aetiology of idiopathic scoliosis: biomechanical and neuromuscular factors small curve develops due to a small defect in the neuromuscular control system and a second stage during adolescent growth in which the scoliotic curve is exacerbated by biomechanical factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 74 publications
2
58
0
6
Order By: Relevance
“…Among the hypothesis of AIS etiology, abnormalities in the central nervous system have long been thought a key AIS etiology [29,30]. Disturbance of central nervous system may impair somatosensory function and motor adaptation which lead to asymmetry of neuromuscular condition causing AIS [30,31]. Correspondingly, functional studies in AIS subjects have shown abnormalities in the postural balance and somatosensory function [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Among the hypothesis of AIS etiology, abnormalities in the central nervous system have long been thought a key AIS etiology [29,30]. Disturbance of central nervous system may impair somatosensory function and motor adaptation which lead to asymmetry of neuromuscular condition causing AIS [30,31]. Correspondingly, functional studies in AIS subjects have shown abnormalities in the postural balance and somatosensory function [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Posture is defined as the alignment or orientation of body segments while maintaining an upright position [1]. Posture asymmetries are associated with the risk of progression in IS [2][3][4], can affect functional activities [5,6] and limit participation in active life [7]. The Cobb Angle remains the gold standard to monitor change in scoliosis over time and is calculated from radiographs [8].…”
Section: Introductionmentioning
confidence: 99%
“…Posture asymmetries are frequently observed among persons with idiopathic scoliosis (IS) [31,46], are associated with muscle imbalance [19,21,35,38,41] and can play an important role in scoliosis progression [4,17,35,41,43]. This progression is attributable to biomechanical factors such as modified trunk alignment and body weight influences which create modifications in muscular moments acting on the spine especially during growth spurt [5,17,35,43].…”
Section: Introductionmentioning
confidence: 99%
“…This progression is attributable to biomechanical factors such as modified trunk alignment and body weight influences which create modifications in muscular moments acting on the spine especially during growth spurt [5,17,35,43]. To restore good posture and to prevent scoliosis progression, physiotherapists work on muscle balance.…”
Section: Introductionmentioning
confidence: 99%